Dust Exhaust System For Auger Miners - Objective: (The National Institute for Occupational Safety and Health (NIOSH), 1976)
Reduce respirable dust exposure of workmen operating auger-type continuous mining machines. Approach: An auger miner was fitted with an exhaust system which draws dust laden air through a [scruber] and discharges it behind the line curtain. How It Works: Dusty air is drawn into the space above the coal conveyor and through a scrubber, by two fans mounted side by side above the conveyor. Exhaust from the fans passes through a duct to the side of the auger miner, and into tubing that runs back and into the air return passage formed by the line curtain. See Figure 1. Of the 5,000 cubic feet per minute of air normally entering the working place, 4/5 is drawn out through the dust exhaust system. The system was installed on a Wilcox Mark 20 Miner and tested underground by personnel of the Bureau's Pittsburgh, Pa., Mining and Safety Research Center, under a cost sharing